Perbaikan Sifat Mekanik, Thermal, dan DMA Komposit Polyester Diperkuat Serat Waru/CaCO3 - Suteja, Suteja; Hidayatullah, Syarif (Politeknik Negeri FakFak, 2025)
Natural fibers continue to attract the interest of researchers to develop them as composite reinforcements in automotive and non-construction building interior applications. Basically, natural fiber-reinforced polymer composites are not suitable for applications exposed to heat. Investigating changes in mechanical properties due to temperature increases, this research is very important to conduct. The addition of filler (CaCO3) is known to improve the performance of natural fiber-reinforced polymer composites. This study investigates the physical, mechanical, and thermal properties of polyester composites reinforced with waru fibers with CaCO3 powder filler. The composites were fabricated using the hand lay-up method with a volume fraction of 30% waru fibers and CaCO3 powder with a volume fraction of 0-10%. The density of the polyester composite increased from 1.42 to 1.68 and 1.87 g/cm3 as the volume fraction CaCO3 0-10%. The results of dynamic mechanical analysis (DMA) testing of the polyester composite showed that parameters such as loss modulus, storage modulus, and tan delta also increased with increasing CaCO3 content. Thermogravimetric analysis (TGA) testing also showed increased thermal resistance after the addition of 5% (wt) (STL) and 10% (wt) (ZMB) with a residual combustion of 6.54% and 7.89% for each STL and ZMB composite, respectively. Compared to the TKO composite, it had the lowest combustion residue of 3.61%. Tensile strength and elastic modulus showed the same trend, namely an increase, while the elongation of the composite decreased with the addition of CaCO3 powder. The overall test results showed that polyester composites reinforced with CWf fibers and CaCO3 fillers were suitable for automotive and building interior applications.